Strictly Ballroom (1992): Departure from Traditional Anglo-Australian Discourses or Veiled Confirmation of Old National-Encouragement Mechanisms? - Seco Salvador, Olga (Miscelánea: A Journal of English and American Studies, 2005)
This article explores the ways in which the Australian feature Strictly Ballroom (Baz Luhrmann, 1992) represents on the screen inter-ethnic conflicts between the dominant Australian culture and the Spanish minority. Although the 1990s represent increased interest in the multicultural reality of the country, Luhrmann’s film proves to lack specificity in its treatment of ethnic issues, which remain repressed or submerged under cover of a more ‘politically correct’ attitude that favours the official ‘Austro-centric’ discourse. I will try to demonstrate that, despite the importance of the female Spanish character for the development and resolution of the film’s main conflicts, Strictly Ballroom’s narrative ends up by enhancing over and above everything else, the English and Irish white male values that have traditionally defined the ‘national type’ of Australian culture.
Keywords: Australia; Cinema; Baz Luhrmann; Inter-ethnic; Identity; Discourse